2017
DOI: 10.1016/j.cct.2016.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intervention for Glucose Tolerance In Teens (DIG IT): Protocol of a randomized controlled trial using health coaching to prevent youth-onset type 2 diabetes

Abstract: Background Youth-onset type 2 diabetes (T2D) is a disease that is newly emerging and behavioral strategies for its prevention are limited. Interventions that target the lifestyle behaviors of adolescents, to improve poor dietary quality and reduce excessive sedentariness, promise to reduce the risk of developing T2D. Health coaching is effective for promoting healthy behaviors in patients who have chronic disease, but few experimental studies are in adolescents. This randomized controlled trial, in adolescents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…As such, interventions to improve self‐management are crucial (Powers et al, 2017). Health coaching has been shown to be an effective means of improving adherence to the diabetes treatment regimen, consequently improving glycemic control and reducing diabetes‐related complications (Huang, Chen, Chang, Su, & Lin, 2017; National Academies of Sciences, Engineering, & Medicine, 2017; Pirbaglou et al, 2018; Sherifali, Viscardi, Bai, & Ali, 2016; Sullivan et al, 2019; Wagner et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As such, interventions to improve self‐management are crucial (Powers et al, 2017). Health coaching has been shown to be an effective means of improving adherence to the diabetes treatment regimen, consequently improving glycemic control and reducing diabetes‐related complications (Huang, Chen, Chang, Su, & Lin, 2017; National Academies of Sciences, Engineering, & Medicine, 2017; Pirbaglou et al, 2018; Sherifali, Viscardi, Bai, & Ali, 2016; Sullivan et al, 2019; Wagner et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The patient will be prepared and motivated before performing salat (Macadam, 2013). The previous study showed that the use of the coaching method provides solutions in both the clinic and the community, such as increasing self-efficacy, health education, life quality and the self-treatment of the patient (Bennett et al, 2009;Vanacker et al, 2017;Wagner et al, 2017). Based on the concept of spirituality and spiritual self-care within Orem's selfcare deficit nursing theory, salat is directly influenced by self-care agency and increasing the knowledge and attitude of the patient through the intervention (White, Peters, & Schim, 2011).…”
Section: Introductionmentioning
confidence: 99%